The Impact Of Manager Performance Development on Organizational Performance - Sukaarnawa, I Gusti Made; Wanti, Wanti Arum; Faliza, Nur; Prasetya, Yanto Budi; Kalsum, ER Ummi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Organizational performance, which is the ability to effectively implement strategies to achieve institutional goals, determines the potential success of an organization. The purpose of this research is to present a series of study results on organizational performance through effective leadership styles in order to achieve job satisfaction. A literature review system with compare, contrast, and critique phases of data analysis is used as the research method. The findings show that leaders play an integral role in both organizational success and employee performance. Leadership requires specific skills and competencies to be effective in complex leadership contexts. Social competence and emotional intelligence are needed in every organization to motivate employees to perform to the best of their ability during times of conflict and upheaval. Companies that are focused on improving organizational performance must be able to satisfy employees' job satisfaction, which in turn helps stimulate better employee performance and improve organizational performance.